INTERACTION OF ETHNO-NATIONAL COMMUNITIES WITH EQUAL AND DIFFERENT STATUS IN THE WEST-UKRAINIAN TERRITORIES IN THE EMPIRE TIME - Монолатій, І. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The subjects and tendencies of the West-Ukrainain ethnic and political sphere on imperial space of Habsburgs are analyzed. An author establishes a difference between the natural habitat and dispersion character of residence of Ukrainians, Poles, Jews and other immigration minorities, and also social unstructured of most ethnic and national associations, which lived in Halychyna and on Bukowyna. On imperial space the central and regional legislation determined the «rules of game» of subjects of inter-ethnical co-operation, directed on defense of rights of ethnic minorities. It and was the tool of correlation of ethnic and political conduct of «stranger». Inter-ethnical distance not always meant sense of isolated in more wide public integrity, and then an ethnic group, keeping it identity, had simultaneously consciousness of belonging to greater association. However there were cases, when distance generated estrangement, and dissatisfactions or hostility appeared in place of feeling of more wide association. Such estrangement became the result of impossibility of realization in the certain terms of important for association of ethnic and political orientations, cultural values or economic interests.